Efecto del acondicionador de suelo terracottem sobre el prendimiento y desarrollo de Caesalpinia spinosa Kuntze en la Reserva Pisaca, cantón Paltas, provincia de Loja - Villacrés Maurad, Diego Raphael (2013)
Research was realized in the reserve Pisaca, owned by the Ecological Foundation Nature and Culture International, located in Paltas, and in the municipal nursery of Catacocha city, Installed a trial to determine the effect of TerraCottem on the ignition and development of the species Caesalpinia spinosa Kuntze, plots were installed in final site and nursery level. The species under study was considered due to its high economic potential, profitable and globally NWFP, especially the fine powder is mainly used in the tanning industry (carpets for cars, piece of furniture, clothing and shoes top). The tannic acid is used in the food industry as a clarifying agent in the manufacture of wine, beer and food, and photographic industries, pulp and paper, among others. Gallic acid is used in the pharmaceutical industry for writing inks, lithography and etching process, as an analytical reagent, and others. For final research site, was located an area of sparse vegetation in the reserve, where a separate block was installed at three sites, with similar environmental and topographic conditions, which consisted of 9 plots each and 30 plants per plot, where 810 plants were used throughout the trial, it was essential that the plants are in good condition and the same level plant age. Experimental design was a randomized block in univariate basis with three replications, the following variables were evaluated in a quantitative response and Discrete Type, Type Quantitative: height, diameter, root length and dry biomass and Discrete type: survival. The treatments included 40 g TCU in T1, T2 treatment was used a dose of 50 g of TCU and control plants (T0) was used without any element only earth. The height and diameter measurements were performed every 60 days, survival and biomass at the end of monitoring. In the treatments applied in the final location, it was reported that there are no significant differences in survival levels between treatments, showed a greater than 50% survival in all treatments applied. The average increase in height variables, average increase in basal diameter, leaf biomass and root biomass, we found a higher result for T2, T1 and T0 beating. These results are not statistically significant thus do not reject the null hypothesis of no significant difference in the measurement variables of seedlings of Caesalpinia Spinosa. The purpose of the nursery level test was to determine the effect of TerraCottem under different irrigation frequencies, that is to say, the search for a direct interaction between the applied dose, frequency of irrigation and development of the species used. This involved installing a block with 16 plots of 12 plants each for a total of 192 plants, using an experimental design in randomized block in arrangement bifactorial composed for Factor 1. TerraCottem the respective dose of D, D0 (0 g), D1 (3 g), D2 (6 g) and D3 (9 g) and Factor 2: irrigation frequencies F, F1 (3 days), F2 (6 days), F3 (9 days) and F4 (12 days). By combining the factors and levels were 16 treatments that were applied to establish three repetitions statistical significance between means of the variables of interest, the variables measured for 6 months and were: survival, height and diameter stem, root length, leaf biomass and root biomass. In treatments applied, it was reported that TerraCottem increases water holding capacity of the substrate by 50%, and that a better development of the species Caesalpinea spinosa in T12 and T7 treatments with irrigation frequency 9 days and 6 days, obtaining an average height of 36.17 and 35.86 cm in diameter and 0.70 cm 0.73 in leaf biomass 24.6 g 20.9 g, root biomass and 3.93 g 3.93 g, respectively. Finally, we conducted socialization and validation of the results, in the foundation Nature and Culture International, and forest engineering career, in order to share the experience to stakeholders and can be used on other sites and with other species.